Medieval sport in the 15th century: the main contrast between the chronicle of Álvaro de Luna and the chronicle of Lucas de Iranzo (Agora for Physical Education and Sport, 2021)
Álvaro de Luna and Lucas de Iranzo were the subject of two medieval chronicles. The first deals with events from the first half of the 15th century, up to 1453. The second is a few decades later, from 1458 to 1471. Both contain detailed information relating to the games of physical competence, but there is a great deal of contrast between the two chronicles. In that of Alvaro de Luna, the physical games are more violent, focused on jousting and tournaments and, the second, on dangerous games spears and rods. They are held in court festivals without the presence or participation of the local people. It can be observed that the jousts and tournaments were still similar to the ways of fighting of the "men-at-arms" in the royal battles, as it appears in the chronicle.In the other chronicle, Iranzo, which relates the life of the city of Jaen and its defense against the Nasrids of Granada during the mandate of Miguel Lucas, a revolution in the medieval games is observed. Revolution that presents in its main notes, the relegation of the most violent forms of the sport, proper of jousts and tournaments, the breaking of the social barriers in the sport of its abundant celebrations and the theatricalization of the games. This revolution can only be explained by the personality of Lucas de Iranzo and the isolation of the kingdom of Jaen from the Castilian court.
Keywords: Middle Ages sport; 15th century sport; medieval games; Alvaro de Luna; Lucas de Iranzo